2021
DOI: 10.1001/jamanetworkopen.2021.35184
|View full text |Cite
|
Sign up to set email alerts
|

Development and Use of a Calculator to Measure Pediatric Low-Value Care Delivered in US Children’s Hospitals

Abstract: IMPORTANCEThe scope of low-value care in children's hospitals is poorly understood. OBJECTIVE To develop and apply a calculator of hospital-based pediatric low-value care to estimate prevalence and cost of low-value services. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study developed and applied a calculator of hospital-based pediatric low-value care to estimate the prevalence and cost of low-value services among 1 011 950 encounters reported in 49 US children's hospitals contributing to the Pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…on the prevalence and costs of low-value care in 49 American pediatric hospitals, the authors found these services were costly, but prevalence varied widely (from 1% to 60%) across measured services. Measures on bronchiolitis, community-acquired pneumonia, and asthma that have been targeted for quality improvement initiatives such as CW recommendations, have resulted in the most common and expensive overtreated conditions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…on the prevalence and costs of low-value care in 49 American pediatric hospitals, the authors found these services were costly, but prevalence varied widely (from 1% to 60%) across measured services. Measures on bronchiolitis, community-acquired pneumonia, and asthma that have been targeted for quality improvement initiatives such as CW recommendations, have resulted in the most common and expensive overtreated conditions ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, including several recent Pediatric Health Information System database studies, reveal high blood culture collection rates among these three diagnoses, with significant variability noted across hospitals. 8,20–22 Data at our institution suggested similarly high collection rates and highlighted the need for local quality improvement (QI) efforts.…”
Section: Introductionmentioning
confidence: 81%
“…In a nontoxic child with uncomplicated CAP, multiple studies have shown that routine blood cultures are unnecessary given the very low likelihood that a blood culture will be positive or result in a change in management. [4][5][6][7][8] The low utility is partly driven by increased immunization against Haemophilus influenzae type b and Streptococcus pneumoniae, dramatically decreasing bacteremia rates. 9,10 Among SSTI, despite the increasing prevalence of methicillin-resistant Staphylococcus aureus, evidence discourages routine collection of blood cultures in immunocompetent children.…”
Section: Introductionmentioning
confidence: 99%
“…28 They identified low-value care for several conditions totaling approximately $17 million in standardized cost. 28 Obtaining blood cultures in uncomplicated CAP and bronchiolitis were identified as low-value care in both patients evaluated in the ED and hospitalized children, costing a combined total of $232,006 and $556,050, respectively. 28 Prospective application of the study criteria to guide blood culture decisions would reduce low-value care and waste and thus improve the care provided to children.…”
Section: Discussionmentioning
confidence: 99%